Hysteroscopy in recurrent in-vitro fertilisation failure (TROPHY): a multicentre, randomised controlled trial. Issue 10038 (25th June 2016) - El-Toukhy, Tarek; Campo, Rudi; Khalaf, Yacoub; Tabanelli, Carla; Gianaroli, Luca; Gordts, Sylvie S; Gordts, Stephan; Mestdagh, Greet; Mardesic, Tonko; Voboril, Jan; Marchino, Gian L; Benedetto, Chiara; et al.
Summary: Background: The success rate of in-vitro fertilisation (IVF) remains low and many women undergo multiple treatment cycles. A previous meta-analysis suggested hysteroscopy could improve outcomes in women who have had recurrent implantation failure; however, studies were of poor quality and a definitive randomised trial was needed. In the TROPHY trial we aimed to assess whether hysteroscopy improves the livebirth rate following IVF treatment in women with recurrent failure of implantation. Methods: We did a multicentre, randomised controlled trial in eight hospitals in the UK, Belgium, Italy, and the Czech Republic. We recruited women younger than 38 years who had normal ultrasound of the uterine cavity and history of two to four unsuccessful IVF cycles. We used an independent web-based trial management system to randomly assign (1:1) women to receive outpatient hysteroscopy (hysteroscopy group) or no hysteroscopy (control group) in the month before starting a treatment cycle of IVF (with or without intracytoplasmic sperm injection). A computer-based algorithm minimised for key prognostic variables: age, body-mass index, basal follicle-stimulating hormone concentration, and the number of previous failed IVF cycles. The order of group assignment was masked to the researchers at the time of recruitment and randomisation. Embryologists involved in the embryo transfer were masked to group allocation, but physicians doing the procedure knew of group assignment and had hysteroscopy findings accessible. Participants were not masked to their group assignment. The primary outcome was the livebirth rate (proportion of women who had a live baby beyond 24 weeks of gestation) in the intention-to-treat population. The trial was registered with the ISRCTN Registry, ISRCTN35859078. Findings: Between Jan 1, 2010, and Dec 31, 2013, we randomly assigned 350 women to the hysteroscopy group and 352 women to the control group. 102 (29%) of women in the hysteroscopy group had a livebirth after IVF compared with 102 (29%) women in the control group (risk ratio 1·0, 95% CI 0·79–1·25; p=0·96). No hysteroscopy-related adverse events were reported. Interpretation: Outpatient hysteroscopy before IVF in women with a normal ultrasound of the uterine cavity and a history of unsuccessful IVF treatment cycles does not improve the livebirth rate. Further research into the effectiveness of surgical correction of specific uterine cavity abnormalities before IVF is warranted. Funding: European Society of Human Reproduction and Embryology, European Society for Gynaecological Endoscopy.